Leviathan's shadow: The imperial legacy of state capacity and economic development in the Kingdom of Yugoslavia - Magnus Neubert (European Historical Economics Society (EHES), 2023)
What is the effect of state capacity on economic development? I argue that strong and centralised states are capable of mobilising the resources required to establish an efficient administration and provide public goods, which are preconditions for modern economic growth. To test this hypothesis, I consider the long-lasting division of Yugoslavia between the Habsburg and the Ottoman empire whose state capacity diverged enormously. I introduce a novel dataset of decomposed GDP, industrial labour force shares and state capacity of 344 micro-regions in Yugoslavia shortly after the dissolution of those empires. By applying a spatial regression discontinuity design along the imperial border, I find that the Habsburg empire had a substantial positive effect on economic development and state capacity. Three types of causal mechanism analysis allow me to estimate the causal effect of state capacity on economic development. I find that a one standard deviation increase in state capacity enhances GDP per capita by 8-11% and the industrial labour force by 21-29%. My results shed new light on the medium-term effects of state capacity on economic development and the mechanisms at work.
Keywords: H41; H70; N14; O18; O43; R12; 330; State Capacity; Economic Development; Habsburg Empire; Yugoslavia